2015
DOI: 10.1017/s0022215115000936
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery programmes in head and neck surgery: systematic review

Abstract: Considerable evidence is available supporting enhanced recovery in head and neck surgery that could be of benefit to patients and which surgeons should be aware of.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The high sensitivity, fast time response, and biodegradability of our sensor means that it could also be of value in biomedical applications beyond orthopedic rehabilitation monitoring. For example, it could be relevant to cardiovascular patches 26 and reconstructive surgery 27 , where the monitoring of mechanical deformations and pressures real time in vivo will allow for refined and personalized medicine. Future research will consist of developing a wireless system made entirely of biodegradable materials, including the circuit used for wireless transmission of measured signals though the skin.…”
Section: Discussionmentioning
confidence: 99%
“…The high sensitivity, fast time response, and biodegradability of our sensor means that it could also be of value in biomedical applications beyond orthopedic rehabilitation monitoring. For example, it could be relevant to cardiovascular patches 26 and reconstructive surgery 27 , where the monitoring of mechanical deformations and pressures real time in vivo will allow for refined and personalized medicine. Future research will consist of developing a wireless system made entirely of biodegradable materials, including the circuit used for wireless transmission of measured signals though the skin.…”
Section: Discussionmentioning
confidence: 99%
“…25 To date, ERAS has been implemented in various surgical specialties. 4,5,7,22,30,38,41,45,49,57 As the earliest discipline to implement ERAS, colorectal surgery offers a substantial body of literature supporting its benefits. 10 For example, a meta-analysis of 16 randomized controlled trials (RCTs) of patients undergoing colorectal surgery found a significant reduction of overall morbidity and LOS with use of an ERAS protocol.…”
mentioning
confidence: 99%
“…3,4 In addition, the last 2 decades have seen greater emphasis on safety, quality, and perioperative management in an effort to optimize patient outcomes. 5…”
mentioning
confidence: 99%